2012
DOI: 10.1007/s11605-012-1855-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Roux-en-Y Gastric Bypass vs Sleeve Gastrectomy on Glucose and Gut Hormones: a Prospective Randomised Trial

Abstract: LRYGB and LSG markedly improved glucose homeostasis. Only LSG decreased fasting and postprandial ghrelin levels, whereas GLP-1 and PYY levels increased similarly after both procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(99 citation statements)
references
References 43 publications
2
81
0
2
Order By: Relevance
“…Since rats consume large meals shortly after dark onset, we suspect that these meals were followed by episodes of severe hypoglycemia and would be consistent with reports of postprandial hypoglycemia in patients after RYGB surgery possibly reflective of an increased incretin response and/or relative of increases in ␤-cell mass of a magnitude greater than that observed in animals that underwent SG (27,35,37). Notably, clinical studies indicate that postprandial GLP-1 release does not differ significantly between RYGB and SG (28,34). Further, a recent pilot experiment in our laboratory using real-time telemetric recordings of blood glucose levels in nondiabetic Wistar rats indicated that RYGB rats had much larger fluxes in glycemia compared with sham-operated controls, which extended into the hypoglycemic range (unpublished data), which is also consistent with continuous glucose monitoring in humans after RYGB (17).…”
Section: Discussionsupporting
confidence: 86%
“…Since rats consume large meals shortly after dark onset, we suspect that these meals were followed by episodes of severe hypoglycemia and would be consistent with reports of postprandial hypoglycemia in patients after RYGB surgery possibly reflective of an increased incretin response and/or relative of increases in ␤-cell mass of a magnitude greater than that observed in animals that underwent SG (27,35,37). Notably, clinical studies indicate that postprandial GLP-1 release does not differ significantly between RYGB and SG (28,34). Further, a recent pilot experiment in our laboratory using real-time telemetric recordings of blood glucose levels in nondiabetic Wistar rats indicated that RYGB rats had much larger fluxes in glycemia compared with sham-operated controls, which extended into the hypoglycemic range (unpublished data), which is also consistent with continuous glucose monitoring in humans after RYGB (17).…”
Section: Discussionsupporting
confidence: 86%
“…The initial search identified 581 publications, of which 576 were excluded, leaving 5 publications for analysis. [14][15][16][17][18] One study, 19 which was the subset of another study, 14 was excluded; another study 20 was the republication of the trial by Woelnerhanssen and colleagues 15 and was also excluded. The 5 trials of LRYGB and LSG for morbid obesity or T2DM with a total of 396 patients that we included in our analysis were retrieved from the electronic databases.…”
Section: Discussionmentioning
confidence: 99%
“…56, No. 6, December 2013 15 Helmiö et al 16 Kehagias et al 17 R a m ón et al 18 or less 1 year after randomization than those patients receiving medical therapy alone. Notably, many patients in the surgical group, particularly those in the gastric bypass group, achieved glycemic control without the use of diabetes medications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid improvement of fasting glucose, insulin secretion and insulin resistance has been reported within days of Roux-en-Y gastric bypass (GBP) [3][4][5] and sleeve gastrectomy (SG) [6,7]. Hypocaloric dieting has also been shown to restore normal glucose levels [8,9].…”
Section: Introductionmentioning
confidence: 99%